Seepage Behavior of an Inclined Wall Earth Dam under Fluctuating Drought and Flood Conditions - Wei Ye; Fuheng Ma; Jiang Hu; Ziyang Li (Geofluids)
Most dam seepage safety analyses evaluate a stable seepage field, infiltration line, and seepage flow. However, under fluctuating drought-flood conditions, the soil surface becomes cracked, making it too complicated to conduct a routine seepage analysis. In this paper, the seepage characteristics of an inclined wall dam under fluctuating drought-flood conditions were studied using a large-scale physical model. The results show that after drought, the permeability coefficient of clay with low crack development was smaller than that of the saturated permeability, but for cracked areas, with high permeability, permeability coefficients were much larger than those of the saturated permeability. As the water level rose, cracks could heal themselves, but this healing was superficial, and the soil could no longer return to its predrought state. After crack healing, the integrity of the dam slope was much less than its original state. In addition, the formation of cracks increased the porosity of the soil and changed the soil permeability, which permanently weakened the antiseepage performance of the clay soil. This study evaluated the seepage flow behavior of an inclined wall dam under fluctuating drought-flood conditions, and results can be used to monitor and protect the weak parts of seepage dams in practical engineering projects.